ฤทธิ์ชีวภาพของสารสกัดจากมะยมในการยับยั้งสื่อสัญญาณแคลเซียม การยับยั้งจุลินทรีย์ และการต้านอนุมูลอิสระ - จันทร์กลั่น, รัฐดา; สิทธิจันทร์, ศุภญา; คงคาทิพย์, งามผ่อง (Thai Journal of Science and Technology, 2019)
Crude ethanol extracts of leaf and stem of Phyllanthus acidus (L.) Skeel were investigated on its biological activities i.e. the inhibition of hyper-activated Ca2+ signaling, antimicrobial growth and antioxidants activity. The Ca2+-signal inhibitory activity was performed using Saccharomyces cerevisiae zds1D-growth base assay on YPD soft agar supplemented with 165 mM CaCl2. Crude leaf extract exhibited inhibitory activity on Ca2+-signal when 5.00 and 1.67 mg of sample were used, while crude stem extract could not attenuate the hyper-activated Ca2+-signal inhibition growth of the strain. Antimicrobial activity of crude extracts was accomplished by disc diffusion following broth microdilution and agar dilution assays. Results showed that crude stem extract inhibited growth of tested-microorganisms such as Enterobacter aerogenes TISTR1540, Bacillus subtilis TISTR008, Staphylococcus aureus TISTR885 and Saccharomyces cerevisiae TISTR5013. The S. aureus TISTR885 was demonstrated the highest susceptibility on crude stem extract with 7.81 and 31.25 mg/mL for minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC), respectively. Crude leaf extract inhibited growth of Candida albicans TISTR5779 with 31.25 and 125 mg/mL for MIC and minimum fungicidal concentration (MFC), respectively. However, both of crude ethanol extracts could not inhibit growth of Escherichia coli TISTR780 at 1,000 mg/mL of crude extract concentration used. Furthermore, antioxidant activity using the DPPH and ABTS assay of crude stem extract was higher than that of crude leaf extract. Crude stem extract exhibited the IC50 value on scavenging activity of DPPH and of ABTS cation radical with 30.34 and 46.09 µg/mL, respectively. In addition, total phenolic content of crude stem and leaf extract was 68.95±0.02 and 47.37±0.01 µg GAE/mg crude extract, respectively.